PTU-027 Colonoscopy Withdrawal Time in Non-Screening Colonoscopies. 6 Minutes or Not?. (17th August 2016) - El-Feki, M; Wilson, R; Hopper, A; Thoufeeq, MH
Abstract : Introduction: Several studies have shown that, in screening colonoscopies, ADR is significantly related to endoscopists with a colonoscopy withdrawal time (CWT). 1 A CWT of more than than 6 minutes is recommended. Studies have also demonstrated that if the endoscopists aware of being monitored they might increase their CWT (the Hawthorne effect). The bowel cancer screening program actively monitors the CWT of endoscopists to ensure that all colonoscopies are of adequate quality but non-screening colonoscopies are not routinely monitored in the same way. Methods: We prospectively looked at 19 endoscopists' practice of colonoscopy of 210 procedures. This included 10 gastroenterologists and 9 non-gastroenterologists. We calculated their withdrawal time by looking at time duration between caecal and rectal retroflexion images. Exclusion criteria included procedures that were incomplete, poor preparation, screening patients, patients in whom polyps were found and planned therapeutic procedures. In order to avoid 'Hawthorne effect', endoscopists were unaware that they were being monitored. Subsequent to that we did a statistical analysis to see if withdrawal time correlated with adenoma detection rate. The ADR was available from the unit's annual endoscopy audit. Results: CWT was less than 6 minutes in 20% of procedures. The mean CWT varied greatly among endoscopists. The mean CWT was significantly longer where the endoscopist was a gastroenterologist rather than a non-gastroenterologist (p = 0.0003). All of the endoscopists that had a mean CWT less than 6 minutes were part of the non-gastroenterologist group. Although we found ADR levels lower in mean CWT of less than 6 minutes and a positive correlation, this however did not reach statistical significance(p = 0.62). Conclusion: In our study we found in majority of the non-screening colonoscopies, withdrawal time was more than the recommended 6 minutes. Statistically significant correlation between ADR and withdrawal in non-screening colonoscopies may be achieved by participating in large multi-centred studies. Reference: 1 Lee TJ, Blanks RG, Rees CJ, Wright KC, Nickerson C, Moss SM, Chilton A, Goddard AF, Patnick J, McNally RJ, Rutter MD. Longer mean colonoscopy withdrawal time is associated with increased adenoma detection: evidence from the Bowel cancer screening programme in England. Endoscopy 2013;45 (1):20–6. Disclosure of Interest: None Declared